IIUM TESL pre-service teachers' motivation to integrate critical thinking in their teaching - Khalid, Madihah; Mansor, Majdina (2017)
This study explored IIUM TESL pre-service teachers’ motivation level to integrate critical thinking in their teaching and the influence of ‘year of study’ towards their motivation. A total of 106 TESL students from Kuliyyah of Education, IIUM participated in a questionnaire survey that measures motivation on a 5-point Likert scale. The data were analysed quantitatively using descriptive statistics and One-Way ANOVA. The results showed that IIUM TESL pre-service teacher motivation to integrate critical thinking in instruction is high. Nevertheless, it was revealed that although not significant, IIUM TESL pre-service teachers’ motivation was slightly influenced by ‘year of study’. This finding gives an insight into the needs for improvements in certain areas of teacher training to ensure success in integrating critical thinking which is in line with one of the Malaysian Education Blueprint objectives.